Design, analysis and fabrication of chapatti mini making machine / Norshamimie Mohd Nazir and Haszeme Abu Kasim - Mohd Nazir, Norshamimie; Abu Kasim, Haszeme (School of Mechanical Engineering, 2022)
Roti making is frequently regarded as a time-consuming activity due to the level of precision needed to get the desired result. For the making of chapattis, a mini-sized, medium-weight, and portable chapatti mini-making machine was designed and fabricated. This machine has the benefits of functioning under low pressure and being simple to operate. Chapattis of constant thickness and shape can also be produced with this equipment. Although various automatic roti makers are available on the market, there is still a gap in terms of size, price, automation, and ergonomics. If a product can fill these gaps, it has a strong possibility of becoming the next popular household appliance and small business tool. The idea of making this product is to support food entrepreneurs who want to operate a small business and house-kitchen users. This new machine can reduce portability and storage problems because it is smaller in size and lighter than the existing machine.